STRATEGI SUAMI ATAU ISTRI KATOLIK UNTUK MEMPERTAHANKAN IDENTITAS KEAGAMAAN DI PAROKI MARIA TAK BERNODA KEPANJEN - Teresia Noiman Derung (Jurnal Pelayanan Pastoral, 2025)
Interfaith marriage is a phenomenon that continues to grow in modern society, including in the Catholic religion. This research aims to identify socio-religious dynamics in interfaith marriages and explore the strategies implemented by Catholic couples, both husband and wife, in maintaining their religious identity. This study focused on Catholics in the Immaculate Conception Parish of Kepanjen, using a qualitative approach through in-depth interviews, observation and documentation.  The research results show that interfaith marriages pose significant challenges in religious life, including in the practice of worship, children's education, and social interactions with the extended family. To face this challenge, Catholic couples apply various strategies, such as building open communication with their partners, negotiating rules regarding worship, and involving children in church activities from an early age. Additionally, support from the Catholic Church is an important factor in helping couples maintain their religious identity.  This research also found that tolerance and respect for the beliefs of non-Catholic partners are key elements in maintaining harmony in their families. Despite facing various dynamics, Catholic couples at the Immaculate Conception Parish of Kepanjen demonstrate the ability to integrate the values ​​of their faith in family life in an adaptive and inclusive manner. This study provides insight into the importance of pastoral support and community strengthening for interfaith couples in maintaining their religious identity.